Business and Breakthrough: Framing (Expanded) Genetic Carrier Screening for the Public. Issue 9 (2nd September 2017) - Holton, Avery E.; Canary, Heather E.; Wong, Bob
ABSTRACT: A growing body of research has given attention to issues surrounding genetic testing, including expanded carrier screening (ECS), an elective medical test that allows planning or expecting parents to consider the potential occurrence of genetic diseases and disorders in their children. These studies have noted the role of the mass media in driving public perceptions about such testing, giving particular attention to ways in which coverage of genetics and genetic testing broadly may drive public attitudes and choices concerning the morality, legality, ethics, and parental well-being involved in genetic technologies. However, few studies have explored how mass media are covering the newer test, ECS. Drawing on health-related framing studies that have shown in varying degrees the impact particular frames such as gain/loss and thematic/episodic can have on the public, this study examines the frame selection employed by online media in its coverage of ECS. This analysis—combined with an analysis of the sources and topics used in such coverage and how they relate to selected frames—helps to clarify how mass media are covering an increasingly important medical test and offers considerations of how such coverage may inform mass media scholarship as well as health-related practices.